Occurrence of Candida Species in Female Residents of Stella Hostel and Their Antifungal Susceptibility Patterns - Hanson, Asikiya Huldah; Amadi-Ikpa, Chidi Nduka; Dike, Blessing Chucks (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
Candidiasis is a yeast infection which occurs as a result of overgrowth of Candida yeast especially Candida albicans due to weekened immune system and change in the pH of the female vagina. The pathogenesis of C. albicans depends on successful secretion of virulent factors. The production of these virulent factors triggers the change from a non-pathogenic C. albicans to a disease-causing organism which makes it possible for the pathogen to to thrive, survive within the host cell and cause infection as opportunity arises. The aim of this study is to determine the occurrence of Candida spp amongst female students of a tertiary institution in one of the Hostels. A total of 50 high vaginal swab samples were collected using sterile swab sticks with the aid of a speculum and inoculated on Sabouraud Dextrose Agar (SDA) plates and incubated at 370C for up tp 72 hours. Wet preparations were also made from colonies of SDA plates inserted into 1ml of normal saline and examined with X10 and X40 objectives. Occurrence of Candia spp from the study population was 80% with subjects between 20-24 years having the highest occurrence. The findings from study calls for a more targeted health education, improved personal hygiene practices and minimizing antifungal/antibiotic abuse.